EVALUASI KUALITAS LAYANAN WEBSITE MENGGUNAKAN WEBQUAL 4.0 DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) (Studi kasus: Madrasah Aliyah Syamsul Huda Kedungreja) - muhammad asep rosadi; Kuat Indartono (Pixel :Jurnal Ilmiah Komputer Grafis, 2021)
The development of information technology is currently increasing rapidly from year to year. One evidence of technological development or advancement is the presence of the internet. The internet has many important benefits for human life. An example of the benefits of having the internet is its popular website. Website is one type of service or facility provided by the internet which is most widely used for various services in many fields, including education, namely schools. Madrasah Aliyah Syamsul Huda, an Islamic-based high school, which is located in Kedungreja District. Madrasah Aliyah Syamsul Huda uses the website as a medium for delivering information related to Madrasah Aliyah Syamsul Huda to students and prospective students. The better the quality of a website, the more users are interested in accessing the website. The purpose of this study is to measure the service quality of the Madrasah Aliyah Syamsul Huda website, a measurement of the measurement of website users on the level of performance and level of importance. The method in this research is the WebQual 4.0 method which consists of 3 variables, namely usability, information quality, quality of service interaction, this study also uses the IPA (Importance Performance Analysis) method. The population in this study were students, teachers, and the community with a sample of 80 respondents. The results showed that 89.03% of the Madrasah Aliyah Syamsul Huda website services had met the respondents' expectations and the Cartesian Impotance Performance Analysis (IPA) results diagram showed that the variables that were of good quality and had to be maintained were US6, IQ1, IQ4, IQ7, and SIQ3. because it has met the expected performance of the respondent. Meanwhile, the variables that are important and are in priority for improvement are IQ3, IQ5, SIQ1, and SIQ6.